Barack Obama United States President : updated and expanded! - Edwards, Roberta; Call, Ken; Edwards, Roberta (New York : Grosset & Dunlap, 2009)
A short biography of Barack Obama, the first African-American president-elect.
Previously published as: Barack Obama : an American story.
Keywords: Obama, Barack; United States. -- Congress. -- Senate; United States. -- Congress. -- Senate; Presidential candidates -- United States; Presidents -- United States -- Election -- 2008; Legislators -- United States; African American legislators; African Americans; Racially mixed people -- United States; Presidents; Legislators; African American legislators; African Americans; Racially mixed people